The crystal structure of 4-(bis(2-chloroethyl)amino)-2-hydroxybenzaldehyde, C11H13Cl2NO2 - Zhang Xu; Zuo Zhenyu; Chen Lei; Bai Fengjiao (Zeitschrift für Kristallographie - New Crystal Structures)
C11H13Cl2NO2, triclinic, space group P1‾ $P\overline{1}$ , a = 7.2061(4) Å, b = 9.5043(5) Å, c = 9.9747(6) Å, α = 70.249(2)°, β = 70.258(2)°, γ = 80.755(2)°, V = 604.34(6) Å3, Z = 2, R gt(F) = 0.0401, wR ref(F2) = 0.1125, T = 293 K.